An assessment of the impact of natural resources, energy, institutional quality, and financial development on CO2 emissions: Evidence from the B&R nations. (June 2022) - Jiang, Qingquan; Rahman, Zia Ur; Zhang, Xiaosan; Guo, Zhiqin; Xie, Qiaosheng
Abstract: This study aims to assess empirically the effect of natural resources, institutional quality, energy use, financial development, and economic growth on the CO2 emissions of the panel of 57- belt and road (B&R) nations over the period 1995 to 2018. The study used an extended Stochastic Impacts by Regression on Population, Affluence, and Technology (STIRPAT) framework. The evidence from long-run estimates vai Driscoll & Kraay regression indicates that total natural resource rents significantly increase in CO2 emissions, while the natural resources proxies by i) fuel export and ii) metal and ore export also positively influence CO2 emissions. Further energy use is disaggregated by fossil fuel and renewable indicating that i) fossil fuel energy increase while ii) renewable energy mitigate the pollution. Additionally, per capita income, financial development, and urbanization significantly increase CO2, while improvement in the institutional quality curb CO2 in the B&R selected sample nations. It is suggested that the government of these nations need to properly address the issues of rapid urbanization, improve institutions, and reduce the excessive use of fossil fuel energy, while needs to boost the usage of renewable energy to mitigate the pollution. Highlights: This study used the extended STIRPAT model for 57 Belt & Road Nations. Natural resources significantly rise in CO2 emissions. Fossil fuel energy increase while renewable energy usage mitigates CO2. GDP, financial development, and urbanization rise in CO2. Improvement in the institutional quality curbs CO2.